2020
DOI: 10.3390/md18030168
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Technologies for the Extraction of Marine Brown Algal Polysaccharides

Abstract: Over the years, brown algae bioactive polysaccharides laminarin, alginate and fucoidan have been isolated and used in functional foods, cosmeceutical and pharmaceutical industries. The extraction process of these polysaccharides includes several complex and time-consuming steps and the correct adjustment of extraction parameters (e.g., time, temperature, power, pressure, solvent and sample to solvent ratio) greatly influences the yield, physical, chemical and biochemical properties as well as their biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 135 publications
(268 reference statements)
2
119
1
3
Order By: Relevance
“…In modern bandage materials, marine-, plant-, animal-, fungus-derived, or bacterial polysaccharides are used as passive natural polymer matrices. Such remarkable characteristics and unique properties as high biocompatibility, mechanical strength, flexibility, porosity, and biodegradability make natural polymers a very promising material as a framework for wound dressings [69][70][71][73][74][75][76].…”
Section: Classification Of Wound Dressingsmentioning
confidence: 99%
See 3 more Smart Citations
“…In modern bandage materials, marine-, plant-, animal-, fungus-derived, or bacterial polysaccharides are used as passive natural polymer matrices. Such remarkable characteristics and unique properties as high biocompatibility, mechanical strength, flexibility, porosity, and biodegradability make natural polymers a very promising material as a framework for wound dressings [69][70][71][73][74][75][76].…”
Section: Classification Of Wound Dressingsmentioning
confidence: 99%
“…During evolution, these organisms acquired the ability to synthesize a wide range of metabolites and biomolecules, many of which have a unique chemical structure that other organisms do not have [10,[53][54][55][56]76,77]. Polysaccharides from marine algae are of particular interest due to the high resistance, biological activity, and availability of these organisms in large numbers [21,59,61,69,74].…”
Section: Polysaccharides From Marine Algae Used In the Development Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Fucoidan is a water-soluble heteropolysaccharide, derived mostly from brown algae, such as Fucus vesiculosus (Figure 1) [1][2][3][4][5]. Recent studies have shown that the research on fucoidan mainly focuses on two aspects-one is to explore ways to increase the yield of fucoidan [6][7][8][9], while the other is to explore the various pharmacological activities of fucoidan [10][11][12], including anti-inflammatory [13,14], anti-tumor, anti-virus, hypolipidemic, antithrombotic, and so on [15], but less research exists on its mechanism. Owing to the characteristics of high incidence and high mortality of tumor, the prevention and treatment of tumor has become a global research trend.…”
Section: Introductionmentioning
confidence: 99%